Przestępstwo samouwolnienia a system dozoru elektronicznego i praca poza zakładem karnym - Ludźmierski, Wojciech; Tyralik, Mikołaj (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The authors, referring to the problems faced by the Supreme Court, analyse the elements of crime stated in Article 242 § 1 of the Polish Criminal Code, in particular, the phrase “being deprived of liberty”. Taking into account the functions of this provision, they conclude it should be applied neither to persons serving sentences in the electronic monitoring system, nor those employed outside a prison without a guard.